Brahms in the home and the concert hall between private and public performance - Hamilton, Katy 1982-; Loges, Natasha (Cambridge University Press, 2014)
Johannes Brahms was a consummate professional musician, a successful pianist, conductor, music director, editor and composer. Yet he also faithfully championed the world of private music-making, creating many works and arrangements for enjoyment in the home by amateurs. This collection explores Brahms' public and private musical identities from various angles: the original works he wrote with amateurs in mind; his approach to creating piano arrangements of not only his own, but also other composers' works; his relationships with his arrangers; the deeper symbolism and lasting legacy of private music-making in his day; and a hitherto unpublished memoir which evokes his Viennese social world. Using Brahms as their focus point, the contributors trace the overlapping worlds of public and private music-making in the nineteenth century, discussing the boundaries between the composer's professional identity and his lifelong engagement with amateur music-making